1305 nm Few‐Layer MoTe2‐on‐Silicon Laser‐Like Emission. Issue 6 (11th May 2018) - Fang, Hanlin; Liu, Jin; Li, Hongji; Zhou, Lidan; Liu, Lin; Li, Juntao; Wang, Xuehua; Krauss, Thomas F.; Wang, Yue
Abstract: The missing piece in the jigsaw of silicon photonics is a light source that can be easily incorporated into the standard silicon fabrication process. Here, silicon laser‐like emission is reported that employs few‐layer semiconducting transition metal dichalogenides of molybdenum ditelluride (MoTe2 ) as a gain material in a silicon photonic crystal L3 nanocavity. An optically pumped MoTe2 ‐on‐silicon laser‐like emission at 1305 nm, i.e. in the center of the "O‐band" of optical communications, is demonstrated at room temperature and with a threshold power density of 1.5 kW/cm 2 . The surprising insight is that, contrary to common understanding, a monolayer MoTe2 is not required to achieve higher efficiency laser‐like operation. Instead, few‐layer MoTe2 offers a higher overlap between the two dimensional (2D) gain material and the optical mode for sufficient gain. The ability to use few‐layer material opens new opportunities for deploying manufacturing methods such as chemical vapor deposition and thereby brings 2D‐on‐silicon devices a step closer to becoming a scalable technology. Abstract : An optically pumped MoTe2 ‐on‐silicon laser‐like emission at 1305 nm, i.e. in the center of the "O‐band" of optical communications, is demonstrated at room temperature with low threshold power. This few‐layer MoTe2 lasing brings 2D‐on‐silicon devices a step closer to incorporating light source in silicon photonics and becoming a scalable technology.